Rancang Bangun Sistem Pengolahan Biaya Operasional Delivery Bukalapak pada PT. Tigaraksa Satria, Tbk - Ade Septiani; Han Sulaiman; Fajar Erlangga (DoubleClick: Journal of Computer and Information Technology, 2020)
AbstractInformation technology that is developing at this time is very varied, according to the needs of the company, especially operational finance. Utilization of information technology is one way to solve the problems faced in reporting and realization. The purpose of this study is to describe the system that runs on Bukalapak delivery operational processing costs at PT. Tigaraksa Satria, Tbk, designed an integrated and well-structured Bukalapak delivery operational cost management system and described the results of the trial run of Bukalapak's delivery operational processing cost management system. The system design method used is Research And Development.